2011
DOI: 10.1007/s11274-011-0821-4
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 IDI performs better than type 1 for improving lycopene production in metabolically engineered E. coli strains

Abstract: In this study a comparison was made between type 1 and type 2 isopentenyl diphosphate isomerases (IDI) in improving lycopene production in Escherichia coli. The corresponding genes of Bacillus licheniformis and the host (i(Bl) and i(Ec), respectively) were expressed in lycopene producing E. coli strains by pTlyci(Bl) and pTlyci(Ec) plasmids, under the control of tac promoter. The results showed that the overexpression of i(Ec) improved the lycopene production from 33 ± 1 in E. coli Tlyc to 68 ± 3 mg/gDCW in E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 40 publications
4
39
1
1
Order By: Relevance
“…Finally, as a simple measure of the effectiveness of the pathway variants obtained, and to place the observed variation in the context of previously-reported carotenoid biosynthesis, ten clones were picked at random from the astaxanthin pathway library and analysed for their production of lycopene, the first coloured carotenoid in the pathway ( Figure 6). In simple, small-scale batch cultures over 24 h we observed different lycopene concentrations from 0 mg/g DCW to 108 mg/g DCW, a similar range to previous comparable studies (40,70,71) , indicating that the variants obtained here represent effective pathway implementations.…”
Section: Combinatorial Start-stop Assembly Of Metabolic Pathways Provsupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, as a simple measure of the effectiveness of the pathway variants obtained, and to place the observed variation in the context of previously-reported carotenoid biosynthesis, ten clones were picked at random from the astaxanthin pathway library and analysed for their production of lycopene, the first coloured carotenoid in the pathway ( Figure 6). In simple, small-scale batch cultures over 24 h we observed different lycopene concentrations from 0 mg/g DCW to 108 mg/g DCW, a similar range to previous comparable studies (40,70,71) , indicating that the variants obtained here represent effective pathway implementations.…”
Section: Combinatorial Start-stop Assembly Of Metabolic Pathways Provsupporting
confidence: 86%
“…The assembly and analysis of the carotenoid pathway libraries validates Start-Stop Assembly as a platform for the implementation and optimisation of metabolic pathways, as (i) the diversity of colony colour and colony size phenotypes reflects the intended wide exploration of design space, (ii) the effectiveness of pathway variants, reflected by carotenoid colours and lycopene concentrations, indicates the absence of emergent issues caused by novel combinations and arrangements of fusion site sequences, and (iii) all 15 core assembly vectors (Table 1) were successfully used during the construction of these five pathway libraries. The aim of these single-round experiments was to validate the approach, not to maximise production, although the results are encouraging and compare well to other reports (40,70,71) . The observed lack of association between colony colour and colony size ( Figures S22 and S23) suggests that different variants encode similarly productive pathways while imposing very different growth impairments on the host cell, and may reflect trade-offs between transcription and translation (37,72) .…”
Section: Discussionsupporting
confidence: 64%
“…Isopentenyl diphosphate (IPP) isomerase catalyzes the reversible interconversion of IPP to DMAPP and possesses two types of IPP isomerase that show no similarity in their amino acid sequences [ 22 , 23 ]. Type I IPP isomerase (IDI-1) utilizes a divalent metal in a protonation-deprotonation reaction, whereas type II IPP isomerase (IDI-2) requires reduced flavin [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Type I IPP isomerase (IDI-1) utilizes a divalent metal in a protonation-deprotonation reaction, whereas type II IPP isomerase (IDI-2) requires reduced flavin [ 24 ]. In previous reports, type II IDI was shown to perform more efficiently for isoprenoid production than type I IDI [ 22 , 25 ]. Therefore, to further increase the production of β-carotene, the FNI enzyme (isopentenyl diphosphate isomerase), a type II IPP isomerase from Bacillus subtilis , was overexpressed in YJM40 ( E. coli BL21(DE3)/pAC-BETA, pYJM40).…”
Section: Resultsmentioning
confidence: 99%
“…Although the yield of our engineered E. coli harboring only a heterologous lycopene pathway achieved the advanced levels quoted in the literature, many papers have reported that the introduction of a heterologous mevalonate pathway improved production of isoprenoids such as lycopene [16,17,20,35], CoQ 10 [36], α-farnesene [37], terpenoid [38], taxol [39] and amorphadiene [40]. Thus, integration of a heterologous mevalonate pathway into the chromosome of the engineered E. coli CBW12241 ( ΔiclR , P T5 appY ) may further improve lycopene production.…”
Section: Resultsmentioning
confidence: 99%